Penggunaan Metode Quantitative Polymerase Chain Reaction (qPCR) untuk Deteksi Fragmen DNA Babi pada Produk Olahan Daging - Bambang Hermawan; Riska Dwi Nanda; Nadya Nurafifah Andriya; Jakaria Jakaria (Jurnal Ilmu Pertanian Indonesia, 2024)
Using food ingredients and/or processed food products contaminated with pork, whether unintentionally or intentionally, has become a growing concern and issue. This condition encourages the development of an accurate method for specifically detecting the presence or absence of pork contamination. The research was carried out on two different samples: (1) fresh pork to provide an in-house positive control and (2) samples of pork-based processed meat products (floss, meatballs, corned beef, and sausages), tested using DNA markers. The use of samples originating from processed pork food is to determine the effect of the processing process on DNA fragments and the robustness of the extraction method for the detection process used. The research aimed to detect pork DNA fragments using the quantitative polymerase chain reaction (qPCR) method. The study stages were extracting fresh pork and processed products using an RNA extraction kit, DNA extraction kit, and salt extraction, as well as measuring the purity and concentration of DNA/RNA using a spectrophotometer. The RNA extract was converted into complementary DNA (cDNA), and the DNA extract was analyzed using qPCR with specific primers for pork DNA (Sus scrofa). The results showed that the concentration of RNA and DNA extracts was 71.1–296.025 ng/uL and of various purity. All processed meat product samples and in-house positive controls were amplified in the Ct range of 23–28 ng/uL. In this case, the meat processing had no effect on the DNA of the processed meat products analyzed, so DNA fragments could be detected. DNA qPCR was more time efficient than cDNA qPCR because it did not require an RNA reverse transcription step. Keywords: beta actin, cycle threshold, fresh pork, pork DNA, qPCR